2015
DOI: 10.1111/jth.13055
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of edoxaban for treatment of venous thromboembolism: a subanalysis of East Asian patients in the Hokusai‐VTE trial

Abstract: Summary. Background: Direct oral anticoagulants have been evaluated for their efficacy and safety in the treatment of venous thromboembolism (VTE), which comprises deep vein thrombosis and pulmonary embolism. The randomized, double-blind Hokusai-VTE trial demonstrated that 60 mg of edoxaban once daily following initial heparin treatment is non-inferior to heparin overlapped with and followed by warfarin for the treatment of VTE, and is associated with significantly fewer bleeding events. Objectives: To assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 23 publications
(18 reference statements)
3
28
1
Order By: Relevance
“…Three recent studies of VTE conducted in Japan also provide insights into the patient characteristics and treatment patterns and comparative data to our analysis. The JAVA registry study [16] with 1076 VTE patients, the East Asian population (warfarin group) of the Hokusai study [17], and the UFH/warfarin group of the AMPLIFY-J study [18] found a similar distribution of patient characteristics as in our analysis: women (58. Comparing the three studies, the proportion of VTE recurrence was highest in our study (7.2 per 100 patient-years), followed by the JAVA study (4.0 per 100 patient-years) [16], and in the East Asian population of the Hokusai study (warfarin group: 4.5 per 100 patient-years) [17].…”
Section: Discussionsupporting
confidence: 70%
“…Three recent studies of VTE conducted in Japan also provide insights into the patient characteristics and treatment patterns and comparative data to our analysis. The JAVA registry study [16] with 1076 VTE patients, the East Asian population (warfarin group) of the Hokusai study [17], and the UFH/warfarin group of the AMPLIFY-J study [18] found a similar distribution of patient characteristics as in our analysis: women (58. Comparing the three studies, the proportion of VTE recurrence was highest in our study (7.2 per 100 patient-years), followed by the JAVA study (4.0 per 100 patient-years) [16], and in the East Asian population of the Hokusai study (warfarin group: 4.5 per 100 patient-years) [17].…”
Section: Discussionsupporting
confidence: 70%
“…Edoxaban reduced the risk of symptomatic recurrent VTE and clinically relevant bleeding in East Asian patients by 36% and 44%, respectively, in comparison to warfarin (6). …”
Section: Discussionmentioning
confidence: 99%
“…And in patients with right ventricular dysfunction with elevated NT-proBNP levels, a reduction in recurrences was observed in edoxaban group compared with that in warfarin group [47]. When paying attention to Hokusai-VTE trial of East Asia area, Asian patients might get extra benefit from edoxaban compared with warfarin than non-East Asian patients [48]. The major concern was that warfarin may be associated with a higher rate of bleeding in Asians and its efficacy in curing thrombosis was sometimes questioned [49, 50].…”
Section: Management Of Pe In China and Japanmentioning
confidence: 99%